Angiotensin converting enzyme inhibitor therapy in children with Alport syndrome: effect on urinary albumin, TGF-β, and nitrite excretion - Kashtan Clifford E; Gauthier Bernard G; Frank Rachel; Futterweit Stephen; Mathew Roy; Adler Liora; Trachtman Howard (BMC Nephrology, 2002)
Abstract Background Angiotensin converting enzyme inhibitors are routinely prescribed to patients with chronic kidney disease because of their known renoprotective effects. We evaluated the effect of short-term therapy with the angiotensin converting enzyme inhibitor, enalapril, in early Alport syndrome, defined as disease duration less than 10 years and a normal glomerular filtration rate. Methods 11 children with early Alport syndrome were investigated. Two consecutive early morning urine specimens were collected at the start of the study for measurement of urinary creatinine, total protein, albumin, TGF-β, and nitrite excretion. Patients were treated with enalapril, ≅ 0.2 mg/kg/day, once a day for 14 days. Two early morning urine specimens were collected on days 13 and 14 of enalapril treatment and two weeks later for measurement of urinary creatinine, total protein, albumin, TGF-β, and nitrite excretion. Results Prior to treatment, urinary excretion of transforming growth factor-β and nitrite, the major metabolite of nitric oxide, was within normal limits in all patients. Administration of enalapril for 2 weeks did not alter urinary albumin, transforming growth factor-β, or nitrite excretion. Conclusion These findings suggest that early Alport syndrome represents a disease involving exclusively intrinsic glomerular barrier dysfunction. At this stage of the illness, there is no evidence of angiotensin II-mediated proteinuria or increased production of transforming growth factor-β and, therefore, routine treatment with an angiotensin converting enzyme inhibitor may not be warranted.